Gizi Kesehatan Reproduksi Remaja di Pondok Pesantren As’ad Kota Jambi - Iin Indrawati; Siti Fati Hatussaadah; Maryam Novitasari (Jurnal Abdimas Kesehatan (JAK), 2025)
Nutrition determines the physical condition of adolescents as well as the ability to concentration while learning and determining health as adults. The main meal is only available for lunch and dinner, while breakfast is usually filled with buying food in school environments of different types. There is no control of the cottage whether santri ate breakfast and the type of food consumed. This condition is feared to impact santri health because it is not met nutritionally as needed by the body. Participants of this activity are santri at Pondok Pesantren Asad Kota jambi, totaling 36 santri. Activities aim to increase santri knowledge of the importance of balanced nutrition for the growth and development process especially in the reproductive organs. The output is to increase the knowledge of santri in choosing balanced nutrition so that there are no health problems in the reproductive system in the future. The implementation method is carried out with lectures, discussions and evaluations of activities in the form of pre-post test related to the material provided. Activities are conducted 6 months while the implementation of Health Education is carried out on 22 November 2023 at Pondok Pesantren As’ad City Jambi. The result of the activity is the increase in knowledge of the santri on reproductive health nutrition by looking at the pre and post test results of 60% that can answer correctly when pre test increases to 100% during post test. It is expected that the management of pesantren makes new tenacies related to the fulfillment of healthy breakfast for the santri and maintain even improve the menu for lunch and dinner to fulfill the nutrition of reproductive health of the santri as a teenager who is in the phase of growth and development.